2019
DOI: 10.4103/jisp.jisp_555_18
|View full text |Cite
|
Sign up to set email alerts
|

Most effective method for the management of physiologic gingival hyperpigmentation: A systematic review and meta-analysis

Abstract: Background and Aim: Gingival hyperpigmentation is an esthetic problem. The aim of the present study was to identify most effective treatment modality for managing generalized physiological gingival pigmentation. Materials and Methods: A systematic review and meta-analysis were done (1919 to October 2018) using PubMed, CINHAL, Dental and Oral Science, and manual searches. Twenty-five articles were finally reviewed. Only human clinical trials were considered with physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
(186 reference statements)
0
19
0
1
Order By: Relevance
“…Bhat et al compared the tissue response post gingivectomy with scalpel or diode laser and observed that the soft tissue margins are more stable after laser excision whereas creeping was observed at 2 months post scalpel excision [14]. Gul et al [15] in their systematic review and meta-analysis observed that diode laser resulted in better aesthetic outcomes after gingival depigmentation and was the modality of preference in terms of patient comfort and satisfaction as compared to other techniques. Jacob et al [16] in their split mouth study found that operative ease was better and recurrence was lower in patients where diode laser was used for depigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Bhat et al compared the tissue response post gingivectomy with scalpel or diode laser and observed that the soft tissue margins are more stable after laser excision whereas creeping was observed at 2 months post scalpel excision [14]. Gul et al [15] in their systematic review and meta-analysis observed that diode laser resulted in better aesthetic outcomes after gingival depigmentation and was the modality of preference in terms of patient comfort and satisfaction as compared to other techniques. Jacob et al [16] in their split mouth study found that operative ease was better and recurrence was lower in patients where diode laser was used for depigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they present smaller rates of melanic repigmentation over time compared to other lasers [ 2 , 7 ]. The majority of soft-tissue procedures performed with diode lasers have output power between 2.5 and 1.5 W, continuous wave, with fiber activation, and these parameters create adequate power to cut tissue, with the fiber always placed directly on the tissue surface (contact mode) [ 8 ]. On the other hand, the usage of pulsed mode in diode lasers is possible, even though they can lead to gingival fenestrations and bone exposure, caused by the lack of control over temperature rise in gingival tissue [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique is slower than spray technique. (10) Disadvantages: (15) Diode laser: This laser is a solid-state semiconductor that utilizes light energy from electric energy. Flexible quartz fiber optic hand piece can be used.…”
Section: Cryoprobe Techniquementioning
confidence: 99%